Analysis of Marketing Psychology: Understanding Consumer Behavior and its Implications for Business Strategy - Supriyanto, Supriyanto; Utami Ady, Sri; Sayidah, Nur (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Marketing psychology is a critical field that examines the cognitive, emotional, and social factors influencing consumer behavior and decision-making processes. In an era where consumer preferences evolve rapidly and brand loyalty is highly competitive, understanding the psychological underpinnings of consumer actions has become essential for businesses. This article explores the relationship between psychological theories and marketing strategies, with a focus on how emotions, perceptions, and mental biases shape purchasing decisions. It also discusses the application of psychological principles in consumer engagement, advertising, and brand positioning. By reviewing contemporary literature on the subject, this article highlights key psychological models such as the Theory of Planned Behavior, Maslow’s Hierarchy of Needs, and the Fogg Behavior Model, illustrating their relevance in modern marketing practices. Additionally, it emphasizes the role of psychological insights in developing personalized marketing strategies and fostering long-term customer relationships. The findings suggest that businesses that effectively apply marketing psychology can enhance their customer experience, increase engagement, and ultimately drive higher sales and brand loyalty. This article aims to contribute to the growing body of knowledge in marketing psychology and provide valuable insights for both academics and practitioners in the field.